Early disruptions to syringe services programs during the Russian invasion of Ukraine - Nikitin, Benjamin M.; Bromberg, Daniel J.; Pykalo, Iryna; Ivasiy, Roman; Islam, Zahedul; Altice, Frederick L. (Frontiers in Public Health, 2023)
Introduction The widespread HIV epidemic in Ukraine is concentrated among people who inject drugs (PWID), making access to sterile injection paraphernalia (SIP) like sterile needles and syringes a critical method of HIV/AIDS prevention; however, the Russian invasion has threatened to disrupt the operations of syringe services programs (SSPs), creating a risk of HIV outbreaks among PWID. Methods We conducted 10 semi-structured interviews with outreach workers from SSPs. Interviews were purposively sampled to cover three prototypic regions of Ukraine: temporarily Russian-controlled, frontline, and destination. Qualitative results from interviews were then compared against a standardized, nationwide harm reduction database. Results We found that the Russian invasion triggered both supply and demand challenges for SSPs. Demand increased for all regions due to client transitions from pharmacies that closed to SSPs, increases in illicit drug use, greater client openness to NGO support, and displacement of clients to destination regions. Supply decreased for all areas (except for remote destination regions) due to battle-related barriers like curfews, roadblocks, and Internet disruptions; diminished deliveries of SIP and funding; and staff displacement. Time series plots of the number of unique clients accessing harm reduction services showed that an initial decrease in service provision occurred at the start of the war but that most regions recovered within several months except for Russian-controlled regions, which continued to provide services to fewer clients relative to previous years. Conclusion To ensure continued scale-up of SIP and other HIV prevention services, the SyrEx database should be leveraged to serve as a streamlined harm reduction locator that can inform workers and clients of open site locations and other pertinent information.